Finite element analyses of cold-formed steel unlipped channel beam with web openings in web crippling - Selvarajasarma, K.; Vithurshan, S.; Janarthanan, B. (My University, 2020)
In recent years, the use of Cold-formed steel has increased as an economical replacement to hot-rolled steel sections due to its high strength to weight ratio. However, these sections are vulnerable to bearing failures due to their high width to thickness ratio. Unlipped channel sections are conventional sections used as joists and bearers in the floor systems of residential and industrial buildings. Their web crippling strengths are considerably reduced when web openings are included for the purpose of locating building services. The available current cold-formed bearing capacity design specifications such as AISI S100 and AS/NZS 4600 signified capacity reduction factors due to circular web openings only for one-flange load cases. The effects of circular web openings of unlipped channel sections with unfastened supports under two-flange load case are still unknown. Hence a numerical study was undertaken in this research to investigate the effects of centred beneath web openings on web crippling behaviour and capacity of unlipped channel sections under End Two Flange (ETF) load case. Developed finite element models using ANSYS were validated with past researches and further used to conduct the detailed parametric study. The results from finite element analyses were confirmed that available current design equations are inadequate to determine the web crippling capacities of unlipped channel steel beams without web openings. Hence the suitable coefficients were proposed to the current design equations of cold-formed steel sections without web openings. Also, it is unconservative to use these design equations to with web opening sections. Therefore, a reduction factor equation needs to be proposed for unlipped channel sections with centred beneath web openings under ETF load case.
Keywords: Cold-formed steel; Unlipped channel